Serial and persistent innovation in UK small companies - Corradini, Carlo (2013)
In this thesis, we endeavour to explore the characteristics and the role of exceptionally innovative small and medium sized enterprises (SMEs) within the UK system of innovation. The focus is placed on 'serial' and 'persistent' innovators, defined as independent companies with an unusually high frequency of innovation over time. The aim of the thesis is to identify such companies and analyse those factors, both internal and external to the enterprise, which influence such a sustained stream of innovation within SMEs.